Análise de estrutura de piso misto formado por vigas treliçadas em perfis formados a frio e lajes pré-moldadas de concreto - Leal, Luiz Alberto Araújo de Seixas (2019)
The steel and concrete composite constructions are widely adopted in order to guarantee optimized material consumption, improved resistant capacity and flexural stiffness associated to the strcutural members. Several scientific researches aim at alternatives to ensure an efficient interaction between both materials and, at the same time, allow the exploitation of the better structural qualities related to steel and concrete. In this context, the main objective of the present work is associated to the experimental investigation and development of floor systems, composed by thin-walled trussed beams and one-way prefabricated concrete slabs, in order to evaluate the static and dynamic behavior of composite floors in terms of Ultimate Limit State (ULS) and Serviceability Limit State (SLS). Additionally, three new innovative solutions for shear connectors, constituted by thin-walled elements, connected to the trussed beams by means of self-drilling screws. The structural behavior of the connection between steel and concrete was investigated through push-out tests, according to the recommendations established by the Eurocode 4, and full-scale bending tests. The experimental results indicated that the connectors are adequate, in terms of resistant capacity and deformation capacity (ductility), to ensure full interaction between the steel trusses and the one-way concrete slabs. Furthermore, the experimental data, obtained from the full-scale tests revealed that the composite behavior produces a considerable benefit associated to bending capacity and flexural stiffness, compared to bare steel trusses.